2013
DOI: 10.1515/polyeng-2013-0127
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of virgin and recycled chloroprene rubber (vCR and rCR) on the properties of natural rubber/chloroprene rubber (NR/CR) blends

Abstract: The effects of various ratios of virgin chloroprene rubber (vCR) and recycled chloroprene rubber (rCR) with a constant content of carbon black (CB) on the properties of natural rubber/chloroprene rubber NR/CR blends were studied. The minimum torque (M L ), maximum torque (M H ), scorch time, and cure time increased with the addition of both CRs and the effects of rCR were more pronounced than vCR on these properties. The tensile strength and fatigue life of the NR/vCR blends increased with an addition of vCR u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This proved that the rigidity is higher in SBR/WR blends gotten by content of carbon black (CB) presented in waste rubber tire (WR). Last observation had been evidenced earlier by Salleh et al 40 and Ismail et al 41 who elucidated that the incorporation of WR into virgin rubber increased the hardness of polymer matrix. Furthermore, blending of DWR with SBR enhanced the hardness (%) and this manners proved previously by Elnaggar et al 3 Comparatively blends contain DWR have lower hardness due to microwave treatment lead to some chain scission and creates new active sites for further reaction with SBR.…”
Section: Hardness (Shore A)mentioning
confidence: 55%
“…This proved that the rigidity is higher in SBR/WR blends gotten by content of carbon black (CB) presented in waste rubber tire (WR). Last observation had been evidenced earlier by Salleh et al 40 and Ismail et al 41 who elucidated that the incorporation of WR into virgin rubber increased the hardness of polymer matrix. Furthermore, blending of DWR with SBR enhanced the hardness (%) and this manners proved previously by Elnaggar et al 3 Comparatively blends contain DWR have lower hardness due to microwave treatment lead to some chain scission and creates new active sites for further reaction with SBR.…”
Section: Hardness (Shore A)mentioning
confidence: 55%
“…Moreover, the unsaturated chemical structure of NR makes it vulnerable to weather elements such as oxidative ageing and ozone attack [6]. To overcome the above-mentioned limitations, NR is frequently blended with polar elastomers such as chloroprene rubber (CR) [7][8][9][10] or relatively less polar and less unsaturated elastomers such as bromobutyl rubber (BIIR), etc., [11] and curing the same with proper curing agent. It is well-known that the most appropriate curing system for the NR is the accelerated-sulfur system.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been reported on the use of recycled rubber in virgin rubber blends [1][2][3] as an alternative for excessive reuse of recycled rubber in industries. This method is useful in reducing environmental waste; it is also economically beneficial.…”
Section: Introductionmentioning
confidence: 99%